Historical review of seagrass research in Malaysia before 2001. - Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah; Shigeo, Kawaguchi (2012)
This historical review of the seagrass research in Malaysia before 2001 includes the results of the effort for nearly one hundred years in the country. As an inventory of seagrasses and their diversity, total 14 seagrass species (belonging 8 genera from 3 families) have been recognized. Although seagrass biomass data are not much, an example of data set including several species at one locality is shown and compared to those of Indonesia. The other information on the 80 seagrass locations high-lighting habitats and species composition, the associated fauna and flora, the utilization seagrasses and seagrass beds, etc. is summarized and tabulated.